A sensitive and specific multiplex PCR approach for sex identification of ursine and tremarctine bears suitable for non‐invasive samples. (25th January 2013) - Bidon, Tobias; Frosch, Christiane; Eiken, Hans G.; Kutschera, Verena E.; Hagen, Snorre B.; Aarnes, Siv G.; Fain, Steven R.; Janke, Axel; Hailer, Frank
Abstract: We report a new approach for molecular sex identification of extant Ursinae and Tremarctinae bears. Two Y‐specific fragments ( SMCY and 318.2 ) and one X‐specific fragment ( ZFX ) are amplified in a multiplex PCR, yielding a double test for male‐specific amplification and an internal positive control. The primers were designed and tested to be bear‐specific, thereby minimizing the risk of cross‐amplification in other species including humans. The high sensitivity and small amplicon sizes (100, 124, 160 base pairs) facilitate analysis of non‐invasively obtained DNA material. DNA from tissue and blood as well as from 30 non‐invasively collected hair and faeces yielded clear and easily interpretable results. The fragments were detected both by standard gel electrophoresis and automated capillary electrophoresis.